Acute Hepatitis B and Syphilis Coinfection in an Immunocompetent Patient with a Prosthetic Aortic Valve - Habibe Tulin Elmaslar Mert; Merve Aytekin; Ertugrul Topcu; Zerrin Yulugkural; Figen Kuloglu (Journal of Global Antimicrobial Resistance)
BACKGROUND: Patients with prosthetic aortic valve (PAV) require warfarin for prophylaxis of thromboembolic complications. International normalized ratio (INR) is utilized to monitor the safety and efficacy of warfarin therapy; an INR goal of 2.5 to 3.5 is generally recommended. AIM: This case report discusses the challenges faced in managing a patient with acute hepatitis B and syphilis coinfection on warfarin therapy. CASE: A 62-year-old man with hypertension, diabetes, coronary artery disease presented with malaise, fatigue, anorexia, persisting for the last month. He had undergone PAV replacement four months ago and was on warfarin therapy since then. During the operation, eight units of erythrocyte suspension was administered.His laboratory results; alanin aminotransferase (ALT):1394 U/L, aspartate aminotransferase (AST):1164 U/L, alkaline phosphatase (ALP):242 U/L, total bilirubin:3.5 mg/dL. His Anti-HBc IgM, HBsAg, Anti-HBe were positive; HBeAg, Anti-HBs were negative. Due to an INR of 3.54, tenofovir disoproxil therapy was initiated to prevent fulminant liver failure. However, his INR increased to 9.38, necessiteting the discontinuation of warfarin and the initiation of vitamin K and fresh frozen plasma. When we observed a biphasic pattern in ALT levels, hepatitis delta antibody, RPR, TPHA were tested. Hepatitis delta antibody was negative, RPR was ½ positive, TPHA was 1/640 positive, although he had no signs and symptoms of secondary syphilis. Penicillin G benzathine 2.4 million units IM was administered once. CONCLUSION: When we observe a biphasic pattern of ALT levels during an acute hepatitis B infection, both hepatitis delta and syphilis should be thought in the differential diagnosis.